The impact of skid trails on the physical properties of tropical hill forest soils - Jusoff, Kamaruzaman; Nik Ab. Majid, Nik Muhamad (Universiti Pertanian Malaysia, 1986)
A field study was conducted in Sungai Tekam Forest Reserve of Pahang, Malaysia to evaluate the effects of skid trails on some selected soil properties. Results showed that bulk density and resistance to penetration increased while total pore space and aeration porosity decreased significantly. The available water holding capacity returned to normal after two years of exposure. This information is useful to forest and land managers who are attempting to manage soils to reduce soil compaction and erosion on skid trails and plan reforestation programmes. Research efforts should aim at reducing the alteration of some soil physical properties on skid trails by proper harvesting practices and reduction of skid trail related disturbances.